(untitled) (Contemporary Journal of Social Science Review, 2024)
This study examined the role of emotional intelligence (EI) in effective management decision-making among middle and senior management professionals across various industries. Utilizing a quantitative approach, a sample of 200 participants was surveyed using the Emotional Quotient Inventory (EQ-i) and a decision-making effectiveness scale. The analysis revealed significant correlations between EI components—specifically motivation, empathy, and self-awareness—and decision-making outcomes. Findings indicated that higher EI levels contribute to improved decision-making effectiveness, highlighting the necessity for organizations to foster EI development within their management teams. These insights offer valuable implications for enhancing organizational performance in complex environments.